2023
DOI: 10.1002/wics.1611
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance limits for mixture‐of‐normal distributions with application to COVID‐19 data

Abstract: Tolerance intervals (TIs) are widely used in various applications including manufacturing engineers, clinical research, and pharmaceutical industries. TIs can be used to construct limits of control charts for monitoring quality characteristics. For manufacturing processes where multiple factors may contribute to defects or multiple‐stream processes, a mixture distribution of several suitable probabilistic models may be a better choice than a simple distribution for modeling the data. TIs for the normal mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…could potentially contribute to the pathogenesis of myocardial infarction, RA, and periodontitis (Figure 3). The global outbreak of coronavirus disease 2019 (COVID-19) originated from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), marking the emergence of a pandemic since late 2019 [100,101] . COVID-19 has resulted in a variety of neurological or other complications [102,103].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…could potentially contribute to the pathogenesis of myocardial infarction, RA, and periodontitis (Figure 3). The global outbreak of coronavirus disease 2019 (COVID-19) originated from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), marking the emergence of a pandemic since late 2019 [100,101] . COVID-19 has resulted in a variety of neurological or other complications [102,103].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients with DM or hyperglycemia exhibit mortality and severity of the disease two to four times higher than those without DM [108]. The potential for The global outbreak of coronavirus disease 2019 (COVID-19) originated from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), marking the emergence of a pandemic since late 2019 [100,101]. COVID-19 has resulted in a variety of neurological or other complications [102,103].…”
Section: Discussionmentioning
confidence: 99%
“…Herbal medicines were natural and have been shown to have good effects in controlling infectious diseases. The coronavirus disease 2019 (COVID-19), which resulted in a global pandemic, was caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ [34] , [35] , [36] ]. Promising outcomes were observed in the treatment of COVID-19 through the combined approach of herbal medicine and Western medicine [ 37 ].…”
Section: Effect Of Treatmentmentioning
confidence: 99%
“…Wang [69] X A thorough examination revealed that an optimal. Exponentially weighted moving average (EWMA) control chart outperformed both the Shewhart and cumulative sum charts in monitoring deaths in the USA.…”
Section: Pakistanmentioning
confidence: 99%